Technologically Distorted Conceptions of Punishment - Jessica M. Eaglin (Washington University Law Review, 2019)
Much recent work in academic literature and policy discussions suggests that the proliferation of actuarial—meaning statistical—assessments of a defendant’s recidivism risk in state sentencing structures is problematic. Yet scholars and policymakers focus on changes in technology over time while ignoring the effects of these tools on society. This Article shifts the focus away from technology to society in order to reframe debates. It asserts that sentencing technologies subtly change key social concepts that shape punishment and society. These same conceptual transformations preserve problematic features of the sociohistorical phenomenon of mass incarceration. By connecting technological interventions and conceptual transformations, this Article exposes an obscured threat posed by the proliferation of risk tools as sentencing reform. As sentencing technologies transform sentencing outcomes, the tools also alter society’s language and concerns about punishment. Thus, actuarial risk tools as technological sentencing reform not only excise society’s deeper issues of race, class, and power from debates. The tools also strip society of a language to resist the status quo by changing notions of justice along the way.
Keywords: Mass Incarceration; Actuarial risk tools; Sentencing reform; Sentencing guidelines; Recidivism risk